Anthropological perspectives on economic development and integration - Dannhaeuser, Norbert, 1943-; Werner, Cynthia Ann, 1967- (Research in economic anthropology ;, 2003)
The collection of original contributions in this volume of Research in Economic Anthropology addresses two recurrent themes in economic anthropology. These are the process of economic development and the basis on which economic integration takes place. The development theme is divided between papers that are concerned with the social and demographic impact of development, and those that examine the recent post-socialist transition. The integration theme is represented by articles that examine the symbolic foundations of economic integration, and by contributions that focus on the moral basis of integration and continuity. With respect to both themes theoretical issues are discussed, and detailed ethnographic cases are drawn from Asia, Europe, Russia, Latin America, and the U.S.